An innovative application of nuclear magnetic resonance technology to complex flows - Hong, Jiaju (2016)
In the present work, an inter principle research is carried out on complex fluid flow and heat transfer, using an innovative technology Nuclear Magnetic Resonance (NMR), from the Department of Physics. To enhance heat transfer performance of complex fluid flow, the present work mainly focuses on two different parts, one is the adoption of nanofluid; the other is flow forces analysis through bionic engineering studies on plant water migration system. Nanofluids are attracting considerable attention from both academic and industrial communities. Comparing with conventional pure fluids or solutions, nanofluids have higher thermal conductivity, due to the high surface to volume ratio of nanoparticle and liquid interface, which exhibits a great potential in enhancing heat transfer performance in various occasions. It is believed that different types and concentrations of nanofluid could strongly affect the thermal performance, and a great number of papers have been published to illustrate the phenomenon. However, none has really focused on the possible concentration change of nanofluid while flowing. Otherwise, the thermal performance of nanofluid flow could never be quantified. In the present work, a novel method to measure the dynamic concentration of nanofluid is proposed, using NMR technology. The experiments were carried out with ferrofluid under different concentration and temperature. A new parameter T2* was introduced in the study. T2* is a relaxation time of the signals that is released by hydrogen atoms after Radio Frequency (RF). And this signal intensity can be strongly affected by nanofluids. Experiments were carried out to obtain the T2* of nanofluid in the pipe. An empirical equation based on T2* and temperature was proposed to calculate the concentration of nanoparticles. Then, experiments were carried out with flowing ferrofluid in pipe. The dynamic concentration was calculated with the empirical equation. And with the series of experiment, it is confirmed that the flowing nanofluid consists of an obvious concentration gradient, and thus cause different layers of thermal performance from boundary to central line of a laminar pipe flow. Furthermore, the experiment result also gives out a chance to investigate the mechanism of nanoparticle movement in laminar flow with the concentration gradient along radius. Bionic Engineering is another research field that has been more and more interesting to researches from various fields. Since life has been evolving for over millions of years, many functions in lives has become extremely high efficiency and adaptive. These functions can be very worthy for researchers to study and utilize in industries. For heat transfer in fluid flow, it is very important to enhance the flow pattern. And thus water migration system in plants become very attractive. Plant can take water from soil up to several metres high. Learning from the water migration process in plants has been attracting interests from scientist for over a hundred years. The water migration in plant stem, especially xylem, involves various driving forces including capillary effect, osmosis effect, Marangoni effect and transpiration effect, etc. This present work mainly focuses on the water transport process within xylem. As xylem system is simplified as micro channel, a mathematic model is presented based on micro channel theory, with critical analysis and simplification. With a simplified micro channel from xylem structure and the calculation using the model of water migration in xylem, the relationship between various forces and water migration velocity is identified. The velocity of water migration within the plant stem is considered as detail as possible using all major forces involved. And a full mathematical model is proposed to calculate and predict the velocity of water migration in plants. Comparison between the calculated result and experimental one is made, to confirm the accuracy of the mathematical model. The present work proved that the mathematical model should be enough to predict the water migration in plants, and could also be critical for future water transport prediction in complex fluid flow in industry applications such as heat pipe.